2012
DOI: 10.1007/s12550-012-0127-x
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin M1 in breast milk of nursing Sudanese mothers

Abstract: The presence of aflatoxin M1 (AFM1) in the breast milk of nursing Sudanese mothers was investigated using AOAC official method 980.21 as the extraction method and HPLC with fluorescence detector for separation and detection. Following informed consent, 94 breast milk samples of mothers were collected, and 51 samples were found to be positive for AFM1, with an average concentration of 0.401 ± 0.525 ng g(-1) and a maximum level of 2.561 ng g(-1). The volunteers completed a questionnaire concerning their dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…Researchers found AFM1 levels in breast milk between 60.90 and 299.99 ng/l in Turkey [16]. Besides, some other studies reported that the mean of AFM1 levels was found to be 71 ng/l in Australia, 664 ng/l in Thailand [67], and 401 ng/l in Sudan [65]. Also, in Nigeria, it was shown that 16 % of breast milk was contaminated with AFM1 over 25 ng/l [12].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Researchers found AFM1 levels in breast milk between 60.90 and 299.99 ng/l in Turkey [16]. Besides, some other studies reported that the mean of AFM1 levels was found to be 71 ng/l in Australia, 664 ng/l in Thailand [67], and 401 ng/l in Sudan [65]. Also, in Nigeria, it was shown that 16 % of breast milk was contaminated with AFM1 over 25 ng/l [12].…”
Section: Discussionmentioning
confidence: 98%
“…In literature, Pb, As, Hg, and Cd were widely studied as important toxic heavy metal contaminants found in breast milk [51], and AFM1 was among mycotoxins as natural toxins [9,64,65] In our study, we investigated the levels of these contaminants. This is the first pilot study from Cyprus, where AFM1 and heavy metal levels were measured in breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the studies covered with this survey, more than half of the mothers in Africa with young children are exposed to aflatoxins, which is class I carcinogens. Namely, a high incidence of aflatoxin biomarker AFM1 was found in 54% and 82% of the maternal breast milk in mothers originating from Sudan and Nigeria, respectively (Adejumo et al 2013;Elzupir et al 2012). Furthermore, all analyzed samples from Kenya women showed the presence of AFB1-lysine conjugate (Leroy et al 2015).…”
Section: Mycotoxin Biomonitoring Studies In Africamentioning
confidence: 93%
“…Even breast milk can be a vehicle for the transfer of mycotoxins to babies, since the mycotoxins contained in food ingested by the mother may pass into her milk, continuing childhood exposure to these compounds, initiated in utero [41]. Children's exposure to mycotoxins (and various other toxic compounds) may start immediately after conception, as many contaminants cross the placenta, and continues throughout life, entering the human body through food, water and air [42].…”
Section: Detecting Mycotoxins In Human Breast Milkmentioning
confidence: 99%